REED OVERGROWTH UTILISATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
The rootfelt properties are investigated for development of technologies for Lake’s overgrowth removal and utilisation. The specific energy of disintegration of rootfelt vary from 7,3 to 18,1 kJ/m2 in dependence on methods used for overgrowth partition. The minimal density of rootfelt is 220 kg/m3 at a surface and the density increases to 1050 kg/m3 in deep layers o f overgrowth. The moisture content (dry basis) of rootfelt vary from 800 % to 250 % and organic matter content lower from 96 % to 25 % in dependence on depth and location of rootfelt in watercourse. The suitable methods and technologies are elaborated for rootfelt removal and biomass utilisation for litter, compost production or for production of Constructed Reedbeds for Effluent Treatment.